OTHR-32. The Pediatric Targeted Therapy 2.0 registry: robust molecular diagnostics for precision oncology. (3rd June 2022) - Ecker, Jonas; Selt, Florian; Sturm, Dominik; Sill, Martin; Korshunov, Andrey; Capper, David; Hirsch, Steffen; Dikow, Nicola; Sutter, Christian; Müller, Carina; Sigaud, Romain; von Deimling, Andreas; et al.
Abstract: BACKGROUND: The Pediatric Targeted Therapy (PTT) 2.0 program was established to enable precision oncology for relapsed pediatric oncology patients by performing a set of molecular analyses on tumor samples to improve diagnostic accuracy and to detect actionable alterations. METHODS: International pediatric oncology patients with relapse or progression after standard of care treatment independent of histological diagnosis were included. Required material was an FFPE sample from any disease episode available to perform a DNA methylation array, customized targeted gene panel sequencing (130 genes), RNA Sanger sequencing in selected cases, and a pathway-specific immunohistochemistry (IHC) panel. For sequencing a blood sample was used as paired constitutional DNA, allowing for detection of potential cancer predisposition syndromes. All molecular results were discussed in an interdisciplinary tumor board and reported back to the submitting centers. The clinical impact of reported findings was assessed by a serial questionnaire-based two year follow-up. RESULTS: n=266 patients were registered, the molecular workup was successfully performed for n=263 (99%) patients. The most frequent diagnostic category was central nervous system tumors (n=172/263, 65%). Integrated molecular diagnostics suggested a refined or changed diagnosis in n=95/172 (55%) brain tumors. Actionable targets were detected in n=106/172 (61%) cases. In n=11/155 (7.1%) of brain tumor patients pathogenic or likely pathogenic constitutional DNA variants with clinical relevance were identified, n=5 (45%) of which were previously unknown. Clinical follow-up of revealed that n=11/131 (12%) of brain tumor patients received mechanism-of-action based treatment matched to the molecular findings in PTT2.0. CONCLUSIONS: Molecular diagnostics adds robust and clinically relevant information on diagnosis, actionable alterations, and cancer predisposition syndromes in CNS and other pediatric tumors even when tissue from the current disease episode is limited.